QIRABOX: Kontrol Speaker Murottal Al-Qur’an dengan Perintah Suara Berbasis Internet of Things - Heny Rimadana (POLITEKNIK NEGERI JAKARTA, 2025)
This study aims to design and implement a Quranic murottal speaker control system based on the Internet of Things (IoT), operated through voice commands, with a focus on the needs of visually impaired individuals. The system integrates speech recognition technology with the Aho-Corasick algorithm for command pattern matching and utilizes the MQTT protocol and ESP32 microcontroller as the main control unit. An Android application called